2015
DOI: 10.1007/s00247-015-3385-x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ovarian torsion: a pictorial review

Abstract: Imaging is crucial in expediting the diagnosis and guiding definitive therapy in children with ovarian torsion. This article reviews the multimodality spectrum of imaging findings in pediatric ovarian torsion, focusing primarily on US appearances. We describe predisposing conditions that can lead to torsion, the pathological basis of the radiologic findings in ovarian torsion, and the common diagnostic pitfalls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 35 publications
(56 reference statements)
1
36
0
2
Order By: Relevance
“…The increased incidence of pathology during adolescence is likely secondary to hormonal influence and gonadal growth resulting in an increased frequency of physiologic and pathologic masses. 7,15,29,30 Our pathology findings were consistent with other studies that showed that the most frequently encountered ovarian and tubal lesions were benign, such as paratubal cysts, cystic teratomas, and hemorrhagic/ follicular cysts. Oltmann and colleagues also showed a strong association between AT torsion and a pelvic mass larger than 5 cm.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The increased incidence of pathology during adolescence is likely secondary to hormonal influence and gonadal growth resulting in an increased frequency of physiologic and pathologic masses. 7,15,29,30 Our pathology findings were consistent with other studies that showed that the most frequently encountered ovarian and tubal lesions were benign, such as paratubal cysts, cystic teratomas, and hemorrhagic/ follicular cysts. Oltmann and colleagues also showed a strong association between AT torsion and a pelvic mass larger than 5 cm.…”
supporting
confidence: 91%
“…The mechanism of torsion in women and girls with ovarian masses is likely related to the increased size and weight of the involved ovary. 6,7 Historically, the treatment for AT was oophorectomy on the basis of theoretical concerns, such as leaving a nonviable severely ischemic ovary that might lead to infection or return to the operating room, missing a malignancy, and/or potential for thromboembolism from untwisting ovarian vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding torsed ovaries, the normal function has been shown able to be restored following detorsion 15. Oophorectomy should therefore be avoided except in cases of thromboembolism, peritonitis, and malignancy 6. Five hemorrhagic cysts were resected in the earlier period of this series.…”
Section: Discussionmentioning
confidence: 97%
“…3 Age-specific normal values for ovarian size are not well established, and the suspected ovary should always be compared to the unaffected side. 2 Given the non-specific nature of torsion symptoms, a significant diagnostic delay exists. A recent review reported a median delay of 101 h from first physical examination to surgery, 4 and a study from a single institution reported an average delay for pre-menarchal patients of over 16 h from presentation to surgery.…”
Section: Referencesmentioning
confidence: 99%